Nanotherapeutics with suitable properties for advanced anticancer therapy based on HPMA copolymer-bound ritonavir via pH-sensitive spacers - Machová, Daniela; Koziolová, Eva; Chytil, Petr; Venclíková, Kristýna; Etrych, Tomáš; Janoušková, Olga (European journal of pharmaceutics and biopharmaceutics, 2018)
Ritonavir (RIT) is a widely used antiviral drug that acts as an HIV protease inhibitor with emerging potential in anticancer therapies. RIT causes inhibition of P-glycoprotein, which plays an important role in multidrug resistance (MDR) in cancer cells when overexpressed. Moreover, RIT causes mitochondrial dysfunction, leading to decreased ATP production and reduction of caveolin I expression, which can affect cell migration and tumor progression. To increase its direct antitumor activity, decrease severe side effects induced by the use of free RIT and improve its pharmacokinetics, ritonavir 5-methyl-4-oxohexanoate (RTV) was synthesized and conjugated to a tumor-targeted polymer carrier based on a N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer. Here we demonstrated that polymer-bound RTV enhanced the internalization of polymer-RTV conjugates, differing in RTV content from 4 to 15 wt%, in HeLa cancer cells compared with polymer without RTV. The most efficient influx and internalization properties were determined for the polymer conjugate bearing 11 wt% of RTV. This conjugate was internalized by cells using both caveolin- and clathrin-dependent endocytic pathways in contrast to the RTV-free polymer, which was preferentially internalized only by clathrin-mediated endocytosis. Moreover, we found the co-localization of the RTV-conjugate with mitochondria and a significant decrease of ATP production in treated cells. Thus, the impact on mitochondrial mechanism can influence the function of ATP-dependent P-glycoprotein and also the cell viability of MDR cancer cells. Overall, this study demonstrated that the polymer-RTV conjugate is a promising polymer-based nanotherapeutic, suitable for antitumor combination therapy with other anticancer drugs and a potential mitochondrial drug delivery system.
Keywords: nanostruktury; Drug Resistance, Neoplasm; HeLa Cells; Multidrug resistance; Methacrylates; Hydrogen-Ion Concentration; methakryláty; Clathrin; Polymers; lidé; HeLa buňky; P-glykoprotein; Antineoplastic Agents; Caveolin 1; protinádorové látky; chemorezistence; Anticancer therapy; ATP Binding Cassette Transporter, Subfamily B, Member 1; adenosintrifosfát; klathrin; Drug delivery; endocytóza; Mitochondrial drug delivery; Adenosine Triphosphate; ritonavir; Polymer-based nanotherapeutic; kaveolin 1; polymery; Endocytosis; Nanostructures; HPMA; Ritonavir; koncentrace vodíkových iontů; Cell penetration compound; Humans